Exclusive graphs: a new link among labelings - Rikio Ichishima; Francesc A. Muntaner-Batle; Akito Oshima (Indonesian Combinatorial Society (InaCombS), 2019)
In this paper, we define a strongly felicitous graph to be lower-exclusive, upper-exclusive and exclusive depending on different restrictions for the vertex labels. With these new concepts, we show that the union of finite collection of strongly felicitous graphs, a lower-exclusive one and an upper-exclusive one results in a strongly felicitous graph. We also introduce the concept of decompositional graphs. By means of this, we provide some results involving the cartesian products of exclusive graphs.